Artificial Intelligence Tools in Personalized Language Learning: A Systematic Thematic Review - Kazi Bushra Orpy; Shakere Juyana; Antura Akter (Universitas Pendidikan Mandalika, 2026)
The integration of artificial intelligence (AI) technologies into language learning has become an essential field of research because it promises to adapt educational experiences to individual learners. With the rapid progress of automatic learning algorithms, adaptive learning systems can now immediately analyze learners' progress and adjust content and delivery methods accordingly. This adaptability improves the personalization of linguistic education, allowing students to engage more deeply with the material at their own pace and skill level. This study aims to explore how AI-driven technologies can improve personalized language learning experiences through autonomous learning. This study focuses on adaptive learning systems powered by AI tools such as ChatGPT, DeepSeek, and Duolingo, developing user engagement strategies, and exploring evolving implications for better results in language acquisition. This research uses a systematic thematic review methodology. Following the guidelines from Braun and Clarke (2006), systematically analyzed 59 peer-reviewed studies thematically. They were identified through academic databases (e.g., Scopus, Google Scholar, ERIC, JSTOR, Education Source) published during 2023-2025. Developed themes included AI for student autonomy, pocket teacher AI: feedback and learning apps, AI for diverse demographics and social inclusion, intelligent conversations: chatbots and language models, personalized learning, limitations, and access inequalities. The study shows that personalized learning helps students learn languages better. Students who use advanced AI tools remember more and manage their learning better than with traditional methods. In the end, the implications of this study highlight the potential of AI tools such as ChatGPT, DeepSeek, and Duolingo to enhance language education by facilitating personalized learning and helping learners achieve better language-learning outcomes.